MicroRNAs in Respiratory Disease. A Clinician’s Overview - Brown, Derek (Ann Am Thorac Soc, 2014)
Since their initial discovery in the early 1990s, microRNAs have now become the focus of a multitude of lines of investigation ranging from basic biology to translational applications in the clinic. Previously believed to be of no biological relevance, microRNAs regulate processes fundamental to human health and disease. In diseases of the lung, microRNAs have been implicated in developmental programming, as drivers of disease, potential therapeutic targets, and clinical biomarkers; however, several obstacles must be overcome for us to fully realize their potential therapeutic use. Here, we provide for the clinician an overview of microRNA biology in selected diseases of the lung with a focus on their potential clinical application.